Inflammatory Environment Promotes the Adhesion of Tumor Cells to Brain Microvascular Endothelial Cells - Wang, Ke; Dong, Shuang; Higazy, Doaa; Jin, Lijing; Zou, Qingcui; Chen, Haowei; Inayat, Aakif; Hu, Sheng; Cui, Min (Frontiers in Oncology, 2021)
Cancer patients usually suffer from unfavorable prognosis, particularly with the occurrence of brain metastasis of lung cancer. The key incident of brain metastasis initiation is the crossing of cancer cells to the blood-brain barrier (BBB). Although preventing brain metastasis is a principal goal of cancer therapy, the cellular mechanisms and molecular regulators controlling the transmigration of cancer cells into the BBB are still not clearly illustrated. In order to understand the changes of adhesion molecule expression during the tumor phase, we analyzed the mRNA expression profiles of metastatic brain tissues and TNF-alpha treated cancer cells. To imitate the tumor microenvironment, in vitro model was developed that the low or high metastatic potential lung tumor cells (A549 or H358) were cultured with the human brain microvascular endothelial cells (hBMECs) under TNF-alpha treatment. The analysis of online database indicated an altered expression for adhesion molecules and enrichment of their associated signaling pathways. TNF-alpha treatment activated hBMECs via up-regulating a number of adhesion molecules, including ICAM1, CD112, CD47, and JAM-C. Meanwhile, TNF-alpha induced an increased expression of adhesion molecule ligands such as ALCAM and CD6 in both A549 and H358. Moreover, the expression of adhesion molecules and the ligands was also increased both in A549- or H358-hBMECs co-culture system, which promoted tumor cells adhesion to endothelial cells. These results suggested that the enhanced the interaction between tumor cells and brain microvascular endothelium might facilitate the incidence of metastatic brain tumors and further offer a better comprehension of brain metastasis prevention and treatment.